The Profile of Students' Locomotor Skills Level in Elementary School - Risky Syahputra; Syahrial Bakhtiar; Ibnu Andli Marta; Lucy Pratama Putri (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2021)
Based on the observations, the problem of the study is the low level of fundamental  motor skills development of children, especially locomotor abilities. The population of this study were all students in Kota Pariaman, the random sampling technique was 67 children. The instrument used to obtain data regarding the level of locomotor development of students was the TGMD-2 instrument subtest, namely: run, hop, jump, gallop and skip. Based on the results, it can be seen that: (1) the students 'ability to run on average is at level 3, (2) the students' hop ability is on average at level 3, (3) the jump ability of the students is on average at level 2, (4) the students 'Gallop Ability on average is at level 2, (5) The students' Skip Ability is on average at level 2.